1996
DOI: 10.1128/jb.178.19.5692-5698.1996
|View full text |Cite
|
Sign up to set email alerts
|

A novel developmental stage-specific lectin of the basidiomycete Pleurotus cornucopiae

Abstract: A novel lectin was isolated from mycelia of the basidiomycete Pleurotus cornucopiae grown on solid medium. The lectin was purified to homogeneity by mucin-Sepharose affinity chromatography. The molecular mass of the lectin was 40 kDa under reducing conditions, but the subunits were polymerized through disulfide bridges under physiological conditions. Hemagglutinating activity of this lectin was completely inhibited by 2-mercaptoethanol, indicating that the multimer is active. The activity was also inhibited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…Pleurotus cornucopiae has been reported to synthesize a mycelial lectin in a developmental stage specific manner. This lectin was found localized on the surface of the growing mycelia on solidified medium, whereas mycelia from the broth cultures did not show any lectin activity (Oguri et al 1996). Fungal cultures in broth did not produce as many spores as the mycelia grown on solidified medium, indicating that the lectin activity was not spore specific.…”
Section: Lectin Activity In Aspergillus Speciesmentioning
confidence: 84%
“…Pleurotus cornucopiae has been reported to synthesize a mycelial lectin in a developmental stage specific manner. This lectin was found localized on the surface of the growing mycelia on solidified medium, whereas mycelia from the broth cultures did not show any lectin activity (Oguri et al 1996). Fungal cultures in broth did not produce as many spores as the mycelia grown on solidified medium, indicating that the lectin activity was not spore specific.…”
Section: Lectin Activity In Aspergillus Speciesmentioning
confidence: 84%
“…As shown in Table 2, the hemagglutinating activity of the expression product was inhibited most strongly by N-acetyl-D-galactosamine, and it was also inhibited by D-galactose, D-fucose, and lactose but not by N-acetyl-Dglucosamine, as was the native PCL-M. 6) These results indicate that although glycosylation occurred more than in the case of the native PCL-M, the expression product in P. pastoris is functional. Further studies using this product on the role of PCL-M in the process of fruitbody formation are in progress.…”
mentioning
confidence: 76%
“…[1][2][3] We have reported that in Pleurotus cornucopiae two kinds of lectins were synthesized in a developmental stage-specific manner, one in fruitbodies and the other in mycelial aggregates. [4][5][6][7] The lectin from the mycelial aggregates (PCL-M) is active when the 40-kDa subunit forms a multimer through a disulfide bridge in the presence of Ca 2þ . 6) We cloned the cDNA of the PCL-M subunit, and sequenced (Sumisa, F., et al, unpublished results).…”
mentioning
confidence: 99%
See 2 more Smart Citations